Do trade facilitation provisions in regional trade agreements matter? Impact on trade costs and multilateral spillovers - Yann Duval; Nora Neufeld; Chorthip Utoktham (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2016)
The scope and depth of bilateral and regional preferential trade agreements (RTAs) negotiated over the past 15 years has expanded beyond traditional market access and preferential tariffs to include provisions on a wide range of issues, including trade facilitation. This study is a first attempt to measure the extent to which RTA provisions related to those featured in the WTO Trade Facilitation Agreement (TFA) contribute to reducing trade costs. Inclusion of such provisions in RTAs does not appear to systematically result in their implementation. Nonetheless, we find that TFA-related provisions in RTAs have a statistically significant impact on bilateral trade costs among RTA members. Aid for Trade Facilitation measures and Freedom of Transit provisions are found to be relatively more effective at reducing trade costs between members than other types of trade facilitation measures. Importantly, the discriminatory (preferential) effect of trade facilitation provisions in RTAs is accompanied by a non-discriminatory reduction in trade costs with all trade partners. Multilateral spillovers from trade facilitation measures in RTAs on trade costs are found to exceed any discriminatory effects within three years of an RTA's entry into force, highlighting the complementarity between regional and global trade facilitation initiatives.
Keywords: F1; F5; F6; 330; trade integration; trade facilitation; trade costs; WTO; trade policy; WTO TFA; regional trade agreements (RTAs); free trade agreements (FTAs); multilateral spillovers; discriminatory effects